HETEROGENEITY, UNPRODUCTIVENESS, AND LEISURE (Andamios, Revista de Investigación Social, 2007)
Globalization is very complex in socio-economic terms, with forms of cooperative organization that include a lot of unemployed people, poor people and “new poor people”. In other words, we are faced with a socio-economic heterogeneity that cannot easily be processed by the present institutions. In this context a paradox emerges: although the notions of productivity and social cooperation continue being fundamental in the organization of contemporary socio-economic institutions, their dislocation is increasingly visible as a result of the increase of unemployment and leisure time, that is to say, of unproductiveness. This essay investigates this paradox focusing the relations that Marxist and Liberal theories establish between social cooperation, productivity and leisure.
Keywords: Social cooperation; distributive justice; heterogeneity; unproductiveness; leisure